2018
DOI: 10.1111/jonm.12605
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ readiness for discharge: Predictors and effects on unplanned readmissions, emergency department visits and death

Abstract: Nurse managers can consider the predictors of patients' readiness for discharge, thus the risk of unplanned readmission and death may be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 25 publications
5
55
2
2
Order By: Relevance
“…33 However, Lowthian et al in an Australian cohort study found that those who lived alone were not more likely to return to the ED at 30 days. A Turkish study found that living alone increased sevenfold the rate of ED returns at 30 days.…”
Section: Screening Instrumentsmentioning
confidence: 98%
See 2 more Smart Citations
“…33 However, Lowthian et al in an Australian cohort study found that those who lived alone were not more likely to return to the ED at 30 days. A Turkish study found that living alone increased sevenfold the rate of ED returns at 30 days.…”
Section: Screening Instrumentsmentioning
confidence: 98%
“…A Turkish study found that living alone increased sevenfold the rate of ED returns at 30 days. 33 However, Lowthian et al in an Australian cohort study found that those who lived alone were not more likely to return to the ED at 30 days. 34 Differences between studies can be related to access to care and community resources; in the Australian cohort, 97% had a general practitioner.…”
Section: Screening Instrumentsmentioning
confidence: 98%
See 1 more Smart Citation
“…The condition of unpreparedness of the patient's return will have an impact on the status of the patient after returning including having a high average length of stay, i.e., the patient is treated three days longer than the patient who is prepared (9). Patient characteristics and lack of discharge readiness were assessed to be associated with reduced hospital discharge conditions (10).…”
Section: Introductionmentioning
confidence: 99%
“…Discharge readiness is an indicator to determine the preparation process for return and gives an influence on the risk of readmission (11). Unpreparedness to go home will also increase visits to the Emergency Room (ED), the incidence of unplanned readmission, and the risk of death after 30 days of discharge from the hospital (9). Every 1% increase in readmission in postoperative patients with THA provides an increase in the cost of health care costs by 1.8% (12).…”
Section: Introductionmentioning
confidence: 99%